How to do everything with podcasting - Holtz, Shel (McGraw-Hill, 2007)
Reach a targeted and influential audience using the medium that's gone from underground scene to mainstream. How to Do Everything with Podcasting walks you, step by step, through the process of creating, broadcasting, and promoting your own podcast. You'll get tips for targeting your audience, refining your content, integrating various technologies, and profiting from your podcast. You'll also discover how businesses can use podcasting as a fresh, inexpensive way to communicate with customers, investors, and employees. Subscribe to, download, and listen to podcasts Get the right hardware and software Plan, record, edit, and release your own podcast Incorporate music, sweeps, interviews, and other elements Connect with listeners using blogs, live chats, and user-created content Profit from your podcast through advertising, networking, and merchandising Tap into support services for help with production, hosting, bandwidth, and more Create customer-focused or business-to-business podcasts